2010
DOI: 10.1063/1.3289735
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the horizontally averaged flow structure in a model wind-turbine array boundary layer

Abstract: When wind turbines are deployed in large arrays, their ability to extract kinetic energy from the flow decreases due to complex interactions among them, the terrain topography and the atmospheric boundary layer. In order to improve the understanding of the vertical transport of momentum and kinetic energy across a boundary layer flow with wind turbines, a wind-tunnel experiment is performed. The boundary layer flow includes a 3×3 array of model wind turbines. Particle-image-velocity measurements in a volume su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
256
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 290 publications
(271 citation statements)
references
References 34 publications
12
256
2
1
Order By: Relevance
“…5e). This contrast between TI andē values suggests that vertical velocity variations contribute most to the turbulence enhancement above the turbine rotor layer during the evening transition, consistent with previous wind-tunnel studies (Cal et al 2010) and idealized LES results (Calaf et al 2010), which emphasize the importance of the vertical flux stimulated by wakes.…”
Section: Wind Speed Deficits and Turbulence Generationsupporting
confidence: 77%
“…5e). This contrast between TI andē values suggests that vertical velocity variations contribute most to the turbulence enhancement above the turbine rotor layer during the evening transition, consistent with previous wind-tunnel studies (Cal et al 2010) and idealized LES results (Calaf et al 2010), which emphasize the importance of the vertical flux stimulated by wakes.…”
Section: Wind Speed Deficits and Turbulence Generationsupporting
confidence: 77%
“…As expected from other wind tunnel studies for wind energy [36][37][38], positive values of −uv occur above hub height in the wake. This component of the Reynolds shear stresses is associated with the vertical flux of mean flow kinetic energy by turbulence and remediation of the wake.…”
Section: A Turbulence Fieldsupporting
confidence: 55%
“…Although the turbulence intensity could intuitively be associated with the flow mixing, it has been demonstrated that the Reynolds shear stresses uv, uw, and vw are responsible of the flow kinetic energy transport (Antonia et al, 1986;Cal et al, 2010;Cantwell and Coles, 1983;Escudie and Line, 2003;Hussain, 1983;and Reynolds and Hussain, 1972) and that as such they must be taken into consideration for evaluating the turbulent mixing in a particular region of the flow. For this reason, the last term of Equation (2), which represents the spatial gradients of the flux of mean-flow kinetic energy, has been evaluated in the x-y plane as U ¼ Àuðu 0 v 0 Þ (streamwise mean-flow kinetic energy flux in the radial direction).…”
Section: F Wake Mixingmentioning
confidence: 99%